A relação de intersubjetividade entre o aluno surdo, o professor de língua portuguesa e o tradutor intérprete de Libras - Busch, Daniela Oliveira Almeida (2019)
This research, entitled “The relationship of intersubjectivity between the deaf student, the teacher of Portuguese Language and interpreter translator of Libras” theme of the communication between the teacher of Portuguese Language and deaf students in high schools of a municipality in the northern region the RS. The overall objective aims to investigate the introduction of subjectivity of the deaf student in Portuguese Language classes in high school, in a town north of the State, as well as occurrence of intersubjectivity between the deaf student, the interpreter translator and professor of Portuguese Language. Such research is justified by the opportunity to reaffirm the legitimacy of Brazilian Sign Language as essential for the deaf to constitute a subject, in this context of example. The theoretical approach is based, above all, in writings about the sign language developed by Sacks (2010), Quadros (2004) and Karnopp & Quadros (2004), as well as in the theory of Enunciation, outlined by Benveniste (1976; 2006), as well as study about the Trinity of Enunciation, proposed by Dufour (2000). In relation to methodology, this is a survey of exploratory nature, qualitative and bibliographic, with case study conducted in two schools, located in the northern part of the State of Rio Grande do Sul. The corpus of this work includes the answers of portuguese teachers of high school, who have in their classrooms deaf students, a questionnaire and an interview. This research reveals that the relationship of intersubjectivity between the teacher and the student deaf often is not effective, because the presence of the interpreter translator of Libras does not supply the lack of knowledge the teacher about the peculiarities of the Signs language.